Endüstride aşındırıcılı su jeti tasarımları - YALÇINKAYA, SENAİ (My University, 2003)
Bu makalede aşındırıcılı su jeti (ASJ) sisteminin çalışma ilkesi, endüstride uygulanması ve diğer üretim yöntemleri ile karşılaştırılması sunulmaktadır. Aşındırıcılı Su Jeti imalat endüstrilerinde delme ve kesme gibi işlemler için tasarlanmakta ve uygulanmaktadır. Tipik değerler olarak, 300-700 m/s lülede su jeti hızı, az karbonlu 12 mm kalınlıktaki çelik için 150-200 mm/dak kesme hızı ve 2 µm den büyük yüzey pürüzlüğü verilebilir. ASJ için kesme hızı plazmadan düşük fakat tel elektro erozyondan yüksektir. Kesme sırasında yüksek sıcaklık oluşmadığından ısıl çarpılma ve kısmi yapısal değişiklik gibi riskler söz konusu değildir.

This paper presents working principle, industrial application and comparative studies of the abrasive water jet (AWJ) system with the other manufacturing processes. AWJ system has been designed for and applied to some operations such as drilling and cutting in manufacturing industries method. AWJ is commonly formed by mixing abrasive particles with high velocity water jets in mixing tubes. Typical length to diameter ratio of the mixing tubes is 50 to 100, and water jet velocities are 300 to 700 m/s, and cutting speeds for 12 mm thick mild steel are 150 to 200 mm/min and average roughness is greater than 2 µm. Generally, AWJ is slower than plasma cutting but faster than wire electro discharge machining. Because it cuts without heat generation, there is no risk of thermal distortion and localized structural changes.
Keywords: Aşındırıcılı su jeti; metal kesme; Abrasive water jet (AWJ); metal cutting